Dihydropyridines Allosterically Modulate Hsp90 Providing a Novel Mechanism for Heat Shock Protein Co-induction and Neuroprotection - Roe, Mark S.; Wahab, Ben; Török, Zsolt; Horváth, Ibolya; Vigh, László; Prodromou, Chrisostomos (Frontiers in Molecular Biosciences, 2018)
Chaperones play a pivotal role in protein homeostasis, but with age their ability to clear aggregated and damaged protein from cells declines. Tau pathology is a driver of a variety of neurodegenerative disease and in Alzheimer’s disease (AD) it appears to be precipitated by the formation of amyloid-beta (A-beta aggregates. A-beta-peptide appears to trigger Tau hyperphosphorylation, formation of neurofibrillary tangles and neurotoxicity. Recently, dihydropyridine derivatives were shown to upregulate the heat shock response (HSR) and provide a neuroprotective effect in an APPxPS1 AD mouse model. The HSR response was only seen in diseased cells and consequently these compounds were defined as co-inducers since they upregulate chaperones and co-chaperones only when a pathological state is present. We show for compounds tested herein, that they target predominantly the C-terminal domain of Hsp90, but show some requirement for its middle-domain, and that binding stimulates the chaperones ATPase activity. We identify the site for LA1011 binding and confirm its identification by mutagenesis. We conclude, that binding compromises Hsp90’s ability to chaperone, by modulating its ATPase activity, which consequently induces the HSR in diseased cells. Collectively, this represents the mechanism by which the normalization of neurofibrillary tangles, preservation of neurons, reduced tau pathology, reduced amyloid plaque, and increased dendritic spine density in the APPxPS1 Alzheimer’s mouse model is initiated. Such dihydropyridine derivatives therefore represent potential pharmaceutical candidates for the therapy of neurodegenerative diseases, such as AD.